Will climate change leave some desert bat species thirstier than others?. (September 2016) - Hall, Lucas K.; Lambert, Connor T.; Larsen, Randy T.; Knight, Robert N.; McMillan, Brock R.
Abstract: The combined effects of global climate change and increased anthropogenic use of free water are likely to cause decreases in availability and surface area of water in arid environments. Climate change and water loss are predicted to alter community dynamics, but identifying mechanisms underlying differential responses of species remains a critical conservation challenge. Bats drink in flight and rely on accessible water sources, yet the ability to access water is a function of flight maneuverability. By reducing the size of water sources (to simulate predicted water loss due to climate change/increased human use), we demonstrated species-specific responses by desert bats based on differences in morphology and flight maneuverability. Under natural conditions, less-maneuverable bats selected larger water sources while maneuverable bats exhibited no preference. When we experimentally reduced surface area, larger, less-maneuverable bats experienced a 69% decrease in the proportion of drinking attempts that were successful ( p < 0.05) and increased competition with smaller, maneuverable bats. Our study illustrates how morphology can mediate access to a resource and highlights conservation implications as water becomes more limited in arid environments. Selection for differences in wing morphology and flight ability in insectivorous bats has allowed for coexistence and high species richness at a local scale. However, anticipated reductions in the sizes of water sources due to climate disruption may lead to species with less maneuverability being unable to access water efficiently and facing increased competition from more agile bats.